What predicts instructional quality and commitments to teaching: self-efficacy, pedagogical knowledge or integration of the two? - Leijen, Äli; Pedaste, Margus; Baucal, Aleksandar; Poom-Valickis, Katrin; Lepp, Liina (Frontiers in Psychology, 2024)
The aim of the paper is to identify different groups of in-service teachers based on their general pedagogical knowledge (GPK) and self-efficacy beliefs and to explore potential differences among these groups regarding their instructional quality and commitments to teaching. A sample of 161 in-service subject teachers (science, mathematics, or Estonian language) who taught in lower secondary schools in Estonia were included in the study. Data was collected with a GPK test and self-reported questionnaires on instructional quality and commitments to teaching in the context of an OECD Teacher Knowledge Survey. Based on the cluster analysis, three groups of in-service teachers were identified: “the over-confident” teachers with average self-efficacy and very low GPK, “the competent” teachers with high self-efficacy and GPK, and “the insecure” teachers with low self-efficacy and average GPK. These three types of teachers were different in terms of instructional quality and commitments to teaching. It seemed that teachers’ self-efficacy beliefs are more important than GPK for instructional quality; however, GPK is more important for teachers’ professional persistence illuminating their general sense of professional identity. Implications of these findings for teacher education and teacher retention will be discussed.